Associated factors of home hospice care utilization by the terminally ill older adults: a mixed-methods study - Peng, Jie; Feng, Xiaoling; Cao, Xiaoying; Lai, Lichong; Dong, Pengxin; Wu, Haichen; Chai, Yidan; Huang, Ping; Hai, Dongmei; Li, Caili; Pan, Yanfei; Fan, Dejing; et al. (Frontiers in Public Health, 2025)
ObjectiveGiven the discrepancy between the low utilization rate of hospice care services and the high willingness to choose hospice care, this study aims to identify the factors influencing the utilization among older adults. The findings will provide a foundation for interventions designed to enhance the growth of this service.DesignA mixed-methods study of convergent parallel designs.MethodsIn the quantitative research phase, in January 2024, a convenience sampling method was used to recruit 350 terminally ill older individuals from three hospitals and three communities in Guangxi, China. Face-to-face surveys were conducted using a general information questionnaire, a Home Hospice Care Service Needs Questionnaire, and a Home Hospice Care Service Knowledge, Attitude, and Practice Scale. In the qualitative research phase, semi-structured interviews were conducted with 16 terminally ill older individuals to explore the barriers and facilitators to the utilization of home hospice care services.ResultsA total of 332 (94.86%) older individuals completed the survey, and 45 (13.55%) accepted home hospice care. The identified barriers to utilization included high physiological, psychological, and spiritual needs, as well as families’ feelings of guilt. The facilitators included being of advanced age (≥80 years), having chronic diseases, not needing a caregiver, having high social needs and knowledge scores, and perceiving a significant economic burden.ConclusionThe utilization of home hospice care services by older adults is lower, which is influenced by both subjective and objective factors. The novel identification of ‘families’ guilty’ as a barrier underscores the need for targeted interventions that address emotional and psychological barriers within families. Policymakers should consider these factors when developing strategies to promote the development of home hospice care for older adults, ensuring that interventions are culturally sensitive and economically feasible.